Low-molecular-weight heparin to prevent postpartum venous thromboembolism - Rodger, Marc A.; Phillips, Penny; Kahn, Susan R.; James, Andra H.; Konkle, Barbara A.; for the PROSPER Investigators (Thrombosis and Haemostasis, 2015)
The risk of venous thromboembolism (VTE) is elevated in the postpartum period. Low-molecular-weight heparin (LMWH) reduces the risk of VTE in many settings but is costly, inconvenient and increases bleeding. Randomised controlled trials (RCT) are required to determine if LMWH prophylaxis provides a clinical benefit in high-risk postpartum women. We sought to determine if a placebo-controlled RCT was feasible. We conducted a multi-national, double-blind pilot RCT in “high risk” postpartum women comparing 21 days of prophylactic dose LMWH to identical saline placebo injections. The primary pilot outcome was mean number of recruited women per centre per month. The planned primary outcome for the full trial was symptomatic objectively confirmed VTE or asymptomatic proximal deep-vein thrombosis diagnosed by a screening bilateral leg vein ultrasound at day 21. In six centres, a total of 1,346 potentially eligible women were approached to participate; 968 were ineligible, leaving 378 (31.5%) eligible patients. Of these, only 25 (6.6%) were randomised at a rate of 0.7 per centre per month. The primary reasons for declining participation were to avoid study injections and being too overwhelmed to participate in research. None of the participants had a VTE during follow-up. In conclusion, despite an adequate number of eligible participants, our double-blind RCT design was not feasible due to a very low consent rate. Other experimental approaches may be necessary to generate evidence in this important area of research.
Keywords: Low-molecular-weight heparin; postpartum; randomised controlled trial; thromboprophylaxis; venous thromboembolism